An On-Chip Photon-Counting Reconstructive Spectrometer with Tailored Cascaded Detector Array - Jingyuan Zheng; You Xiao; Mingzhong Hu; Hao Li; Lixing You; Xue Feng; Fang Liu; Kaiyu Cui; Yidong Huang; Wei Zhang (Advanced Devices & Instrumentation, 2023)
The hybrid integration of superconducting nanowire single-photon detectors (SNSPDs) on various substrates and photonic structures has great potential on developing complicated photonic devices based on single-photon detections, such as photon-counting reconstructive spectrometers for the spectral sensing of single-photon level faint light. In this paper, we introduce the cascaded absorption effect of SNSPDs to develop a photon-counting reconstructive spectrometer. The device includes a Rowland grating as the spatial dispersion element and a tailored cascaded SNSPD array in the focusing region of the grating. The spectral responses of the SNSPDs could be flexibly modulated by their coiled patterns and the cascaded absorption in the array, which are used as the bases for spectral reconstruction. A prototype device was designed and fabricated to demonstrate the principle of the scheme. The experiment results showed the feasibility of the spectral response modulations by the coiled pattern design and the cascaded absorption effect of the SNSPD array. It supports the spectral measurement and reconstruction in the wavelength range of 1,495 to 1,515 nm, with a spectral resolution of 0.4 nm. The proposed scheme achieves the bases for spectral reconstruction only by the design of SNSPDs and without the spectral modulation effects of additional photonic structures. It provides an interesting and promising way to develop devices with high photon utilization.